Oxygen Evolution Activity and Chemical Stability of Ni and Fe Based Perovskites in Alkaline Media. Issue 10 (21st July 2018) - Adolphsen, Jens Q; Sudireddy, Bhaskar R.; Gil, Vanesa; Chatzichristodoulou, Christodoulos
Abstract : The electrochemical activity of LaNiO3, La0.97 NiO3, LaNi0.6 Fe0.4 O3, La0.97 Ni0.6 Fe0.4 O3 and La2 Ni0.9 Fe0.1 O4, toward the oxygen evolution reaction (OER) was measured in 1M KOH at room temperature. All materials showed comparable OER activity with Tafel slopes in the range 56–98 mV/dec. The overvoltage at 10 mA·cm −2, measured on a well-defined geometric surface area, was in the range 0.38–0.45 V. The best performing materials among the ones investigated were LaNiO3 (multiphase) and La2 Ni0.9 Fe0.1 O4 . The chemical stability of the stoichiometric materials was also assessed in 31wt% and 45 wt% KOH respectively at 100°C and 220°C. All materials were partially decomposed after 1 week of exposure at 220°C. After 1 week of exposure at 100°C LaNiO3 had formed secondary phases whereas LaNi0.6 Fe0.4 O3 and La2 Ni0.9 Fe0.1 O4 showed only traces of secondary phase. The main secondary phases were in all cases La(OH)3, NiO, Ni(OH)2 and Fe2 O3 . These observations indicate that the investigated oxygen electrode materials are not suitable for operation in alkaline electrolysis cells above 100°C.